MEMBANGUN SISTEM E-COMMERCE DAN PENGENDALIAN PERSEDIAAN SPAREPART MOTOR PADA YERI MOTOR DENGAN MENERAPKAN METODE INVENTORY PROBABILISTIMEMBANGUN SISTEM E-COMMERCE DAN PENGENDALIAN PERSEDIAAN SPAREPART K MENGGUNAKAN BAHASA PEMROGRAMAN PHP FRAMEWORK LARAVEL - Hendriani, Sisi; Adha, Afifah Cahayani (Journal of Hospital Administration and Management (JHAM), 2024)
Yeri Motor sells motorbike spare parts for many types of products and many consumers, but still uses a conventional sales system and does not have inventory management. As a result, owners have difficulty handling sales transactions and managing product inventory. The aim of this research is to create an e-commerce website that can be used to carry out online sales transactions and control products precisely in terms of procurement. The appropriate method to use in inventory control in this case is a probabilistic inventory approach. The inventory control model used is the P model with Back Orders and Lost Sales. This system was created using the PHP programming language, Laravel framework and HTML with a MySQL database. The results of this research show that the application of the system can help companies sell their products online, determine order times and the economic order quantity of a product.